Determinants of prolonged length of stay in the emergency department: A mixed method study from Iran - Hosseininejad, Mohammad; Aminiahidashti, Hamed; Pashaei, Seyede Masoume; Goli Khatir, Iraj; Montazer, Seyed Hosein; Bozorgi, Farzad; Mahmoudi, Fahime (Archives of Academic Emergency Medicine, 2017)
Introduction: Timeliness has been considered as a key domain in quality of emergency department (ED) care and delay in care providing is influential determinants of patient’s outcomes. The present study, aimed to evaluate the determinants of prolonged ED length of stay (LOS). Methods: In this cross-sectional study, using adopted version of the latest form for external evaluation and accreditation of EDs introduced by Iranian Ministry of Health, determinants of prolonged LOS were evaluated in the ED of an educational Hospital. Using SPSS 11, multivariate binary logistic regression was applied to estimate adjusted odds ratios (OR) for determining factors associated with prolonged LOS. Results: 162 (10.2%) cases with prolonged LOS were detected. Based on univariate analysis, female gender (OR: 1.42, 95% CI: 1.14-1.75, p = 0.001), older age (OR: 1.05, 95% CI: 1.02-1.08, p < 0.0001), admission on evening shifts (OR: 4.0; 95% CI: 1.84-8.68, p < 0.001), triage level I (OR: 1.76, 95% CI: 1.21-2.57, p = 0.003), lack of insurance support (OR: 1.56, 95% CI: 1.12-2.19, p = 0.010), higher number of ordered para-clinical tests (OR: 1.23, 95% CI: 1.11-1.37, p = 0.016), and disposition time > 6 hours (OR, 0.13, p < 0.0001), were significant risk factors of prolonged LOS. Conclusion: Older age, lack of insurance support, disposition time > 6 hours due to complexity of patients’ complaint, and the necessity of repeated para-clinical measures were the most important reasons for failed provision of timely services. From the view point of ED personnel, a small part of prolonged LOS in ED was concerned with defective ED workflow, while, the most important cause of such delays was the delayed response of the consultancy services.